Time passes - healthy habits stay? - Saša Pišot; Rado Pišot; Boštjan Šimunič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2022)
Introduction: Because healthy behaviors learned early in life are more likely to be maintained during adulthood, we aimed to investigate longitudinal changes of participants that were regularly involved in extracurricular sport activities (athletes; N = 7; 4 boys) and those that were not (non-athletes, N = 6; 3 boys) Methods: Participants of both groups were invited for re-assessment at the age of 27, in 2019, 12 years after they participated in a 5-year longitudinal study as adolescents (9-14 years of age, in the period 2001‒07). We investigated vastus lateralis (VL) and biceps femoris (BF) contractile properties (tensiomyography), maximal running speed (photocells), anthropometric measures (bioimpedance), maximal vertical jumping height (squat and countermovement jumps on a ground reaction force plate), and lifestyle characteristics (GPAQ and EHIS surveys). Results: Based on Cohen's d effect size we found that athletes have lower body mass index, higher maximal running speed, better maximal vertical jumping height, and shorter BF contraction time, not found in VL, compared to non-athletes. Furthermore, athletes also exhibit healthier lifestyle characteristics such as lower sedentary time and higher daily energy expenditure than non-athletes. Athletes follow diet regimens consisting of more regular meals with more protein and indulge less in health-risk behavior (smoking and alcohol consumption). However, the self-perception of health and quality of life was lower in athletes than in non-athletes. Conclusion: EU regulations and the beginning of the COVID-19 pandemics prevented us from conducting a study on a more representative sample. Nevertheless, we could confirm that regular sport participation yields better physical performance and a healthier lifestyle but could also have a negative impact on health (injuries) and quality of life.